Spatial Variability of Soil Fauna Under Different Land Use and Managements - Silva,Raimunda Alves (2018)
ABSTRACT Geostatistics allows the evaluation of the distribution pattern of data with high spatial variability in agricultural systems. This study aimed to evaluate the spatial variability of biological diversity indices of soil fauna under different land (agriculture and forest). Samples were collected in seven areas (millet, soybean, corn, eucalyptus, pasture crops, and preserved and disturbed Cerrado), in Maranhão state, Brazil. The soil fauna was caught trapped in pitfall traps, installed 3 m away from each other. In each area, 130 traps were maintained for seven days. After this period, they were removed and their content transferred to bottles and taken to the laboratory, where the insects were screened and identified at the level of orders and families. Eight indices were calculated, namely: individuals trap-1 day-1, Jackknife richness estimator, the Simpson, McIntosh, Shannon, and total diversity, and Simpson dominance, and Pielou equitability indices. The spatial variability was derived from the semivariograms fitted to Gaussian, spherical, and exponential geostatistical models. Statistical analysis showed medium values of the coefficient of variation for millet, except for the indices individuals trap-1 day-1 and McIntosh diversity, which were considered high. The values of the correlation matrix were negative for some indices, suggesting an inverse relationship. For millet, corn, eucalyptus, disturbed Cerrado, and pasture areas, the Shannon diversity index exhibited a pure nugget effect. For the areas of millet, corn, disturbed Cerrado and pasture, the total diversity index was adjusted to the Gaussian model. The degree of spatial dependence was considered high for the individuals trap-1 day-1 and Pielou equitability indices for millet. Only for soybean and pasture similarity in the scaled semivariograms was observed for the spatial variability of the indices, indicating similarity of performance. Soil management and land use affect the patterns of soil fauna abundance, richness, and diversity. The presence of groups such as Araneae, Diplura, and Poduromorpha are related to ecological equilibrium, quality, and sustainability of the agricultural systems studied.